Availability, Overlap and Cost of Quality Journal Subscriptions in Computer Science - Zainab, A.N.; Ng, S.L. (Curtin University of Technology, 2004)
This study describes the availability of quality journals held at the University of Malaya Library (UML) in the field of computer science and compares this to the availability of journal collections in four other university libraries: Science University of Malaysia (USM), University of Technology Malaysia (UTM), National University of Malaysia (UKM), and University Putra Malaysia (UPM). All the universities included in the study have been established for more than fifteen years and offer degree programmes in computer science. Quality journals refer to the 301 titles with impact-factor scores listed in the Journal Citation Report 1999 (JCR) in the field of computer science. The study also investigates the degree of journal overlap among the five university libraries. The UML was taken as a case study to show how overlap titles are ascertained and costs calculated. The results indicate that (a) UML holdings of quality journal titles is poor and that a similar pattern is indicated in the other university libraries (34.22% by UML, 40% by UTM, 16% by UKM, 31% by USM, and 23% by UKM); (b) for the five libraries, out of the 301 titles, 115 (38.2%) overlap, 96 titles (32.23%) are singly-held titles, and 84 titles are not subscribed to; (c) the percentage of overlap is related to the size of title availability; (d) the cost of journal title overlap for UML is estimated to be about U.S.41,440.32. It is proposed that cooperative subscription ventures would help reduce costs and release monies to cover the other quality titles not subscribed to by any of the libraries.